Pemanfaatan Limbah Tahu dan Tanaman Indijenes Menjadi Produk Program Kreativitas Mahasiswa Kewirausahaan Eldara Body Scrub - Kumalasari, Indah; Pramudita, Jelita Almas; Kuswara, Rabi'atu Zahra Ardika; Rahmani, Rifdah Aulia; Haryanto, Lorenta In (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: Air quality in Indonesia is declining due to air pollution stemming from high levels of vehicle use and industrial emissions. High levels of air pollution is a trigger for the emergence of free radicals that can harm the health of the skin. Student of Muhammadiyah University of Jakarta innovated natural body scrub products made from tofu waste and indijenes plants without chemicals. The PKM-K Eldara Body Scrub activity was held from June to November 2023. Method: The method used is the diffusion of science and technology, because this activity inventories ideas and knowledge into a product that can be used by the community. Diffusion of Science and technology is done by disseminating knowledge and technology (science and technology) that comes from the source to the recipient or potential user. This activity includes implementation, success indicators and outcomes. Progress can be implemented well through profit and loss indicators and consumer analysis through satisfaction surveys. Result: The result of calculating the profit and loss potential shows a small profit figure, this is due to the small capacity of production tools. Conclusion: Eldara in the eyes of consumers is a product with affordable prices and friendly to the environment, which means this product is in the very good category.